The Anxiety Level between Extrovert and Introvert Students in Speaking English - Mainar - Fitri; Wega Novriewani (Indonesian Journal of Integrated English Language Teaching, 2022)
Students’  performance in speaking English can be influenced by students’ anxiety. This research aimed to find out the difference  of anxiety level between extrovert and introvert students in speaking performance. This research was conducted at one of  senior high schools in Pekanbaru, Riau Province, Indonesia  by using cluster random sampling technique.  The method of the research was not experimental but causal-comparative research. There were two types of questionnaires used to collect the data. The Eysenck Personality Inventory questionnaire was used to classify the extrovert and introvert students, while to find out the speaking anxiety level between extrovert and introvert students, the questionnaire of Foreign Language Classroom Anxiety Scale (FLCAS was used.. By using product moment formula through SPSS 2.4 in analyzing the data, it was found that the sig.t was 0,000, smaller than the sigma alpha of 0,05 (sig.t <0,05). It means that there is a significant difference of speaking anxiety level  between extrovert and introvert students. The percentage score of anxiety level in speaking performance of extrovert students was 106%%. It was categorized as "Low" level. The percentage score of anxiety level in speaking performance of introvert students was 122%. It was categorized as "Medium" level.